Cranberry, but not D-mannose and ibuprofen, prevents against uropathogenic Escherichia coli-induced cell damage and cell death in MDCK cells - Konesan, Jenane; Wang, Jenny; Moore, Kate H.; Mansfield, Kylie J.; Liu, Lu (Frontiers in Microbiology, 2023)
The main function of the urinary tract is to form an impermeable barrier against urinary solutes and bacteria. However, this barrier can be compromised by urinary tract infections, most commonly caused by uropathogenic Escherichia coli (UPEC). This can result in damage to the epithelial barrier, leading to decreased epithelial thickness, loss of tight junctions, loss of epithelial integrity, and apoptosis. Due to the rise in antimicrobial resistance, there is worldwide interest in exploring non-antibiotic agents as alternative therapy. Using the Madin-Darby canine kidney (MDCK) cell line, a widely accepted epithelial cell model for the urinary tract, and the UPEC strain UTI89, this paper aimed to investigate the impact of UPEC on cell integrity, permeability, and barrier functions, and determine whether cranberry, D-mannose and ibuprofen could counteract the effects induced by UPEC. Furthermore, the study examined the protective potential of these agents against UPEC-induced increase in reactive oxygen species (ROS) production and programmed death-ligand 1 (PD-L1) expression. The results demonstrated that UTI89 caused a marked reduction in cell viability and monolayer integrity.Cranberry (3 mg/ml) was protective against these changes. In addition, cranberry exhibited protective effects against UPEC-induced damage to cell barrier integrity, escalation of oxidative stress, and UPEC/TNFα-triggered PD-L1 expression. However, no effect was observed for D-mannose and ibuprofen in alleviating UPEC-induced cell damage and changes in ROS and PD-L1 levels. Overall, cranberry, but not D-mannose or ibuprofen, has a protective influence against UPEC associated damage in urinary epithelial cells.